Exploring EFL Students’ Perceptions of Public Speaking Skills Through a News Anchor Performance Activity - Pipit Rahayu; Eripuddin Eripuddin; Yova Afriansyah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Developing effective public speaking skills is a key objective in English language education, yet many university students experience anxiety and limited opportunities for structured practice. This study investigates students’ perceptions of public speaking skill development through a News Anchor activity implemented in a natural classroom setting. This qualitative study involved 25 second-semester undergraduate students enrolled in a Public Speaking course at the English Department of Pasir Pengaraian University. Data were collected through semi-structured interviews, classroom observations, reflective journals, and analysis of students’ scripts and recorded performances. The data were analyzed thematically, and triangulation across multiple sources was applied to ensure credibility and consistency. The findings reveal three major themes: increased confidence, improved delivery techniques, and stronger language organization. The structured news anchor activity provided students with a clear communicative role and opportunities for repeated rehearsal, which helped reduce anxiety and improve voice projection, pacing, fluency, eye contact, posture, and gestures. Analysis of students’ scripts also indicated clearer content organization and more appropriate use of news-style expressions. Although some pronunciation challenges persisted, students demonstrated greater strategic use of practice and feedback. Overall, the News Anchor activity functioned as an effective performance-based learning strategy that supports the development of public speaking skills. By combining structured roles, rehearsal, and authentic speaking practice, the activity provides a practical approach to enhancing students’ confidence, delivery, and language organization in higher education public speaking courses.